L’administration Eisenhower et le spectre du communisme à Cuba - Salim Lamrani (Études Caribéennes, 2023)
Following the Cuban Revolution in 1959, the Eisenhower administration sought to find out whether the new power, which had expressed its desire for greater independence from the United States, was under Communist rule. During the first two years, from the recognition of the revolutionary government in January 1959 to the unilateral severance of diplomatic relations by Washington in January 1961, the White House sought to forge a link between Havana and Moscow in order to be able to rally the rest of the Latin American continent to its hostile policy towards the island.